Development of a chemical reactor simulation module with MATLAB (SCIÉNDO INGENIUM, 2022)
A tube reactor simulation module based on MATLAB has been developed. For this the units considered were mathematically modeled, from the balances of matter and energy for plug and flow reactor. The obtained models were coded in the language of the program to later compile them through a graphical interface, providing a fast and intuitive means to carry out the corresponding calculations. The supply of the information required for the calculation of the state functions and other parameters is obtained from an attached database, created from the information obtained from the Design Institute for Physical Properties. The results obtained were compared with bibliographic data as well as compared with the values ​​provided by other simulation programs.
Keywords: simulation; processes; reactors; engineering; MATLAB